Extraction of totally impacted lower third molar with CGF (concentrated growth factors) application into a post-extraction bone defect – a case report - Gnatek, Adrian; Janas-Naze, Anna; Osica, Piotr; Chybicki, Damianc (Journal of Education, Health and Sport, 2019)
Concentrated Growth Factors (CGF) are obtained after blood collecting and its centrifuging. As an autogenic material it gains an advantage over xenogeneic materials used in regenerative procedures. Due to high concentration of growth factors and CD34+ cells in such a small volume, CGF promotes tissue regeneration. The following the article presents a case of 32-year-old-patient who underwent the augmentation of the post-extraction bone defect with CGF after the extraction of totally impacted lower third molar. Reduction of post-operative complications was observed.